2019
DOI: 10.3390/cryst9050255
|View full text |Cite
|
Sign up to set email alerts
|

The Fabrication of Calcium Alginate Beads as a Green Sorbent for Selective Recovery of Cu(Ⅱ) from Metal Mixtures

Abstract: Calcium alginate (CA) beads as a green sorbent were easily fabricated in this study using sodium alginate crosslinking with CaCl2, and the crosslinking pathway was the exchange between the sodium ion of α-L-guluronic acid and Ca(II). The experimental study was conducted on Cu(II), Cd(II), Ni(II) and Zn(II) as the model heavy metals and the concentration was determined by inductively coupled plasma optical emission spectrometry (ICP-OES). The characterization and sorption behavior of the CA beads were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 42 publications
6
31
0
Order By: Relevance
“…For the tested systems, the affinity of the Fe_Alg for metal ions was in the following decreasing order: Pb 2+ > Cu 2+ > Cd 2+ > Zn 2+ in DW_PM, and Cu 2+ > Pb 2+ > Cd 2+ > Zn 2+ in SW_PM. Metals’ adsorption in the DW_PM solution is consistent with other reports, in which the adsorption of these metals on calcium-crosslinked alginate adsorbents [ 49 , 50 ], on alginate modified by the grafting of urea maintained [ 51 ] and on activated carbon-containing alginate adsorbent [ 52 ] was studied. An affinity of Fe_Alg for number of metal ions found in the study are consistent with the ability of sodium alginate to bind to multivalent cations following the sequence of Pb 2+ > Cu 2+ > Cd 2+ > Ba 2+ > Sr 2+ > Ca 2+ > Co 2+ > Ni 2+ > Zn 2+ > Mn 2+ [ 53 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For the tested systems, the affinity of the Fe_Alg for metal ions was in the following decreasing order: Pb 2+ > Cu 2+ > Cd 2+ > Zn 2+ in DW_PM, and Cu 2+ > Pb 2+ > Cd 2+ > Zn 2+ in SW_PM. Metals’ adsorption in the DW_PM solution is consistent with other reports, in which the adsorption of these metals on calcium-crosslinked alginate adsorbents [ 49 , 50 ], on alginate modified by the grafting of urea maintained [ 51 ] and on activated carbon-containing alginate adsorbent [ 52 ] was studied. An affinity of Fe_Alg for number of metal ions found in the study are consistent with the ability of sodium alginate to bind to multivalent cations following the sequence of Pb 2+ > Cu 2+ > Cd 2+ > Ba 2+ > Sr 2+ > Ca 2+ > Co 2+ > Ni 2+ > Zn 2+ > Mn 2+ [ 53 ].…”
Section: Discussionsupporting
confidence: 90%
“…The adsorption experiments demonstrated that the beads exhibited a high removal efficiency for the selective adsorption of Cu 2+ . It was due to better bond stability with Cu 2+ compared to other metals [ 50 ]. Research conducted by Chen et al [ 42 ] showed that the nature of lead uptake was the typical ion exchange between Ca 2+ and Pb 2+ at the carboxylate anionic site, whereas the copper uptake took place through the ion exchange between Ca 2+ and Cu 2+ as well as the formation of the coordination complex.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium alginate with abundant carboxylate and hydroxyl groups [ 71 ], reacts with divalent cations such as Cu(II) [ 72 ], and others [ 73 , 74 , 75 ], to form cross-linked hydrogels, existing in reticular structures called “egg box” structures [ 76 , 77 ]. In transition metal-alginate systems, the sol-gel transition is characterized by a complex formation in which only the carboxyl groups in both M and G residues are coordinated to the metal ions [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in peak vibration intensity in the region between 3000 and 3600 cm −1 indicated that Cd 2+ interacts with -OH formed in alginate beads. Hydroxyl groups were also designated as binding sites for Cu 2+ and Zn 2+ on the surface of alginate beads [55].…”
Section: Discussionmentioning
confidence: 99%